Stroke characteristics are associated with sprint-paddling performance in female and male competitive surfers - Gosney, S.; MacDonald, L.; Parsonage, J.; Worsey, M.; Keogh, J.; Chalkley, D.; Meier, B.; Denny, A.; Webster, H.; Minahan, C. (Sports Biomechanics, 2025)
Spatiotemporal kinematics represent a novel domain within surfboard sprint-paddling. Investigating the interplay between stroke characteristics and sprint-paddling speed can inform the development of effective training strategies for both female and male surfers. 31 competitive Australian surfers (n = 15 females, n = 16 males) performed two maximal 15-m sprint-paddling trials in a swimming pool. Split times (5-, 10-, and 15-m), stroke count, stroke rate, stroke length, and stroke phase distances (glide, pull, push, recovery) during acceleration and speed maintenance periods over the 15-m were measured. Regression analyses determined multiple spatiotemporal variables that strongly contributed to faster split times at all distances, including a sex interaction effect (r2 = 0.749, 0.791, and 0.794 respectively). For all surfers, push distance during acceleration and pull distance during speed maintenance were indicative of faster split times. For male surfers, the pull distance during the full sprint-paddle effort was indicative of faster split times. No variables were indicative of faster times for female surfers. This indicated that the development of a technique which promotes longer propulsive distances (i.e. pull and push distance) and an additional investigation of the female surfer should be encouraged to further afford optimal sprint-paddling success in both sexes.